Melestarikan Budaya Peduli Ekosistem Mangrove Bagi Penyuluh Agama dan Organisasi Kepemudaan di Kota Kendari - Sakti, Abdul; Sahindomi Bana; Wiwin Rahmawati Nurdin; Nurnaningsih Hamzah; Abigael Ka’be; Nurhayati Hadjar; Lade Ahmaliun; Pendais Haq; La Ode Dinda; La Ode Marhini; Khabiirun; Agus Rihu (Jurnal Pengabdian Masyarakat Hutan, 2024)
The Kendari Bay mangrove ecosystem has an important role in maintaining the balance of coastal and marine ecosystems, especially as a natural protector from coastal erosion and seawater abrasion, as well as a habitat for various flora and fauna. However, these ecosystems continue to face pressure from human activities, such as deforestation for ponds, reclamation, and coastal development, which are exacerbated by climate change. This community service aims to increase awareness of mangrove sustainability in Kendari Bay, by involving religious extension workers and youth organizations. This activity included socialization about the importance of mangrove conservation and the planting of 300 mangrove seedlings in the area. Religious extension workers, as pioneers in the community, have an important role in spreading a culture of caring for the environment. Similarly, youth organizations act as agents of change that promote the values of environmental care among members and the wider community. Through the collaboration between Halu Oleo University, the Regional Office of the Ministry of Religious Affairs of Southeast Sulawesi, and the Ansor Youth Movement, this program is expected to be able to create conservation cadres and build a culture of caring for the environment. This effort not only focuses on mangrove planting, but also integrates religious and youth values in conservation practices. Thus, this program contributes to the preservation of sustainable mangrove ecosystems in Kendari Bay